Public Relations Management in Building the School Image at Sekolah Indonesia Johor Bahru - Marrom, Mochammad Azza Nurul; Roesminingsih, Erny; Yulianingsih, Wiwin; Khamidi, Amrozi (IKIP Widya Darma Surabaya, 2024)
Objectives: This study aims to explore the role of public relations management in shaping the image of Sekolah Indonesia Johor Bahru (SIJB). Methods: A qualitative case study approach was used, involving interviews, observations, and document analysis. Results: The findings indicate that well-structured PR activities, guided by strategic planning, organization, implementation, and evaluation, significantly enhance the school's reputation. Public relations programs such as the Wonderful Nusantara Festival, Southeast Asian Science, Arts, and Sports Competition, graduation ceremonies, and student creativity programs in collaboration with Indonesian universities have strengthened SIJB's image. In addition, the mass circumcision event has further demonstrated SIJB's commitment to community engagement. Novelty: This study highlights the important role of comprehensive public relations management in enhancing the image of Indonesian schools overseas.